1998
DOI: 10.1073/pnas.95.12.6897
|View full text |Cite
|
Sign up to set email alerts
|

SIRE-1 , a copia/Ty1 -like retroelement from soybean, encodes a retroviral envelope-like protein

Abstract: The soybean genome hosts a family of several hundred, relatively homogeneous copies of a large, copia͞Ty1-like retroelement designated SIRE-1. A copy of this element has been recovered from a Glycine max genomic library. DNA sequence analysis of two SIRE-1 subclones revealed that SIRE-1 contains a long, uninterrupted, ORF between the 3 end of the pol ORF and the 3 long terminal repeat (LTR), a region that harbors the env gene in retroviral genomes. Conceptual translation of this second ORF produces a 70-kDa pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 79 publications
(85 reference statements)
0
75
0
4
Order By: Relevance
“…Copy number of this element may go from a few copies to as high as 10,000 copies per haploid genome in some phyla (Jarvik and Lark, 1998). A family of a copia/Ty1-like retroelement (SIRE-1) has also been characterized (Laten et al, 1998). This family consists of only a few hundred members and each member is approximately 11 kb.…”
Section: Current Status Of Soybean Genomicsmentioning
confidence: 99%
“…Copy number of this element may go from a few copies to as high as 10,000 copies per haploid genome in some phyla (Jarvik and Lark, 1998). A family of a copia/Ty1-like retroelement (SIRE-1) has also been characterized (Laten et al, 1998). This family consists of only a few hundred members and each member is approximately 11 kb.…”
Section: Current Status Of Soybean Genomicsmentioning
confidence: 99%
“…Two SIRE1 elements inserted into same tract of bean genome, the most unusual of which is the SIRE1 element (Laten and Morris 1993), which falls into the STR102 repeats with possible site-specific integration. Later one element was removed via unequal recombinacopia/Ty1 family (Laten et al 1998). Laten et al (2003) found that the flanking sequences of 3 of 10 SIRE1 tion (described below), leaving the solo LTR.…”
Section: ϫ4mentioning
confidence: 99%
“…To confirm that these sequences were enriched specifically in the centromeric regions and not pericentromeric regions, we utilized a previously isolated bacterial artificial chromosome (BAC), 76J21, that localizes to the pericentromeric regions of all 40 chromosomes (Lin et al, 2005) and contains previously described soybean repeats STR120 (Morgante et al, 1997) and the retrotransposon SIRE1 (Laten et al, 1998). FISH of BAC 76J21 in combination with CentGm-1 and CentGm-2 repeats to premeiotic pachytene chromosomes revealed that both centromeric repeats marked the primary constrictions exclusively (Fig.…”
Section: Identification and Cytological Verification Of Centromeric Smentioning
confidence: 99%